Lumbar Intradiscal Ozone Chemonucleolysis Applied Together with the Epidural Steroid Treatment - Kilic, Mustafa (Sisli Etfal Hastan Tip Bul, 2021)
OBJECTIVES: Intradiscal ozone treatment is a minimally-invasive method that can be applied to patients who have low back pain and do not respond to conservative treatment. This retrospectively designed study aimed to evaluate its clinical efficacy, adverse effects, or complication rates. METHODS: Patients with lumbar degenerative disc disease (LDDD) who underwent intradiscal O(2)-O(3) treatment between January 2016 and April 2018 were included in the study. Pain and disability levels were assessed at pre-injection, 1-month and 1-year post-injection periods using visual analog scale (VAS) and Oswestry Disability Index (ODI), respectively. RESULTS: A total of 520 patients (270 males and 250 females) with the mean age of 38.9±5.7 years included in the study. First-month and 1st-year post-injection VAS and ODI scores were significantly lower than pre-injection scores (p<0.001). Remarkable VAS score reduction (more than 50%) was found in 60.2% of patients at 1st month and in 52.9% of patients at the 1st year. No important side effects recorded. CONCLUSION: Intradiscal ozone therapy applied together with the epidural steroid treatment, one of the percutaneous application techniques for the treatment of low back pain related to LDDD, has successful outcomes, clinical efficacy, and low rate of side effects, and thus, is one of the methods that should be considered before surgery when appropriate patients.